Peluang dan Tantangan Industri Media dan Hiburan Halal di Indonesia: Kajian Kelembagaan dari Sudut Pandang Produk Hukum di Indonesia - Utami, Fadia; Sarifa, Siti; Fadilah, Suci Nurul (Diponegoro Journal of Islamic Economics and Business, 2021)
Media industry and halal entertainment industry has a huge potency to be developed in Indonesia. Indonesia as a country with largeest Muslim population in the world should be able to develop this industry. However, the huge potential in this industry has not been matched with the contribution of media and halal entertainment in Indonesia and also inadequate government regulations to regulae this industry to develop mode. Therefore, this study aims to analyse the opportunities and challanges of the halal media and entertainment industry in Indonesia. This study also aims to present a comprehensive regulatory framewor in the halal media and entertainment industry in order to acelerate the Indonesian economy. This study uses legal research, by gathering several articles, and also existing government regulation. The results of this study caan be used as a formula recommenation for comprehensiv regulations on the halal media and entertainment industry in Indonesia.